Protective Efficacy of Thymol on Glycoproteins In Isoproterenol Induced Myocardial Infarcted Rats An In vivo And In vitro Study - Selvaraj, P (International Journal of Pharmaceutical & Biological Archive, 2014)
Protective Efficacy of Thymol on Glycoproteins In Isoproterenol Induced Myocardial Infarcted Rats An In vivo And In vitro Study